2023
DOI: 10.1097/sle.0000000000001162
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Imaging in Laparoscopic Cholecystectomy Plus Laparoscopic Common Bile Duct Exploration: A Suitable Option for Patients With Difficult Exploration (With Videos)

Abstract: Background: The clinical application of indocyanine green (ICG) fluorescence imaging technology in biliary surgery has gradually highlighted its role, and its role in laparoscopic cholecystectomy plus laparoscopic common bile duct exploration (LC+LCBDE) still needs to be further explored. Therefore, we evaluated the clinical value of ICG fluorescence imaging in LC+LCBDE.Materials and Methods: Data from 131 patients who underwent LC +LCBDE in our department between January 2019 and June 2021 were retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Ma’s study, for instance, revealed that patients in the ICG group had a higher BMI compared to those in the control group. 16 Additionally, despite efforts to minimize selection bias, the possibility of residual or unaccounted bias in the included studies cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ma’s study, for instance, revealed that patients in the ICG group had a higher BMI compared to those in the control group. 16 Additionally, despite efforts to minimize selection bias, the possibility of residual or unaccounted bias in the included studies cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…We further analyzed the incidence of bile leakage and bile duct drainage among the total complications. 16,27 We found that the incidence of bile leakage was lower in the ICG group compared to the control group (RR = .27, 95% CI:0.12-.62, P = .002, I 2 = 0) (Figure 4A).…”
Section: Study Selection and Characteristicsmentioning
confidence: 90%
See 2 more Smart Citations
“…In cases involving suspected bile duct anatomical variations or challenging scenarios, such as previous upper abdominal operations, real-time ICG imaging is a favorable option for ductal mapping. It enhances bile duct visibility and reduces postoperative complications and bile leaks[ 61 ]. Although there is no absolute consensus, recent research suggests that the optimal dose and timing for fluorescence cholangiography with ICG were intravenous administration of 10 mg of ICG around 10–12 h before the operation, respectively[ 62 ].…”
Section: Surgical Techniques Of Lcbdementioning
confidence: 99%